2014
DOI: 10.2337/db14-0744
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Early Alterations in Adipose Tissue Biology and Function and Its Association With Obesity-Related Inflammation and Insulin Resistance in Children

Abstract: Accumulation of fat mass in obesity may result from hypertrophy and/or hyperplasia and is frequently associated with adipose tissue (AT) dysfunction in adults. Here we assessed early alterations in AT biology and function by comprehensive experimental and clinical characterization of 171 AT samples from lean and obese children aged 0 to 18 years. We show an increase in adipocyte size and number in obese compared with lean children beginning in early childhood. These alterations in AT composition in obese child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
185
1
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(222 citation statements)
references
References 47 publications
20
185
1
16
Order By: Relevance
“…11,12 Moreover, consistent with our findings here and in previously published work 6 others have shown that larger adipocytes are associated with greater insulin resistance in humans. 7,13,14 Of interest, we found that adipocyte hypertrophy in DM affects specific subpopulations of adipocytes based on size, with decreased adipocytes »700-3,300 mM 2 and increased adipocytes »5,600-8,700 mM. 2 Others have shown that greater improvements in insulin sensitivity are associated with a reduction of large and very large adipocyte subfractions in DM patients after caloric restriction and exerciseinduced weight loss.…”
Section: Discussionmentioning
confidence: 83%
“…11,12 Moreover, consistent with our findings here and in previously published work 6 others have shown that larger adipocytes are associated with greater insulin resistance in humans. 7,13,14 Of interest, we found that adipocyte hypertrophy in DM affects specific subpopulations of adipocytes based on size, with decreased adipocytes »700-3,300 mM 2 and increased adipocytes »5,600-8,700 mM. 2 Others have shown that greater improvements in insulin sensitivity are associated with a reduction of large and very large adipocyte subfractions in DM patients after caloric restriction and exerciseinduced weight loss.…”
Section: Discussionmentioning
confidence: 83%
“…It is possible that prolonged exposure of adipocytes to insulin may increase leptin secretion by a combination of such mechanisms. Furthermore, it has been suggested that a delayed effect of insulin treatment on leptin secretion in adipocytes is compatible with the effect being indirect 12 and additional physiological factors may be involved in vivo with strong candidates being hormonal 34 and inflammatory 35,36 influences, and a role for the hypothalamus. 23 Should the delayed effect of insulin treatment on leptin secretion in adipocytes from type 2 diabetic donors be proven in subsequent studies, the phenomenon may be analogous to the biphasic response of insulin secretion to glucose 37 where impairment of early and late phase insulin secretion leads to different clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between traditional inflammatory cells, cytokines, and chemokines and insulin resistance has been studied in adult populations (10). In children, obesity-related adipose tissue dysfunction develops early in childhood and is related to IR (11). In a previous study in adolescents, an association between IR and some inflammatory biomarkers was observed, and these relationships were stronger in obese subjects (12).…”
Section: Introductionmentioning
confidence: 99%